Procedures for a Non-Patriarchal Writing in "My Life", by Lyn Hejinian - Fernández Folgueiras, Erea (Tropelías: Review of Literary Theory and Comparative Literature, 2025)
This paper aims to examine Lyn Hejinian’s best-known work, My Life, as an example of non-patriarchal writing. Here, “non-patriarchal” refers to a critical perspective that highlights how literary forms reproduce and legitimize a sociocultural system that assumes a masculine, cis-heterosexual, white, and literate subject as universal, favoring narratives that align with his experience. Hejinian’s approach challenges the conventions and implications of autobiography, one of the genres that best fits this model, through procedures that displace and reconfigure the subjectivity that use to be at its center. The goal of this paper is to analyze how two of these procedures, juxtaposition and repetition, impose their linguistic conditions on a text that counters the referential, chronological, and individual tendencies of autobiography with the critical deviations of memory.